PKM. PENTINGNYA KESIAPAN MENTALITAS PARA SISWA SMK WIDYA WISATA GRAHA SEBAGAI CALON TENAGA KERJA YANG HANDAL DI DUNIA PARIWISATA - Yoga Putra Semadi; I Ketut Suardana (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2023)
Widya Wisata Graha Vocational School (WWG) Amlapura is one of the vocational schools in Karangasem Regency that prioritizes skills in the field of tourism. In addition, students get subjects related to tourism as the main support, students must be equipped with strong mental readiness to do a job. Mental readiness is very important because it is closely related to obligations and performance. Mental preparation is obtained through the provision of intensive training providing work motivation. Providing motivation is realized through community service carried out by the English Study Program, Bali Dwipa University on May 29, 2023. Work motivation is provided by dissecting the meaning of a text such as children's song text and the narrative text Pan Balang Tamak. The explanation of the meanings of the two texts is listened to carefully because the meanings of the texts are not understood in depth, but semantically based on the explicit meanings in the text. The implicit translation of the meaning of the text is very important as a guide for students in carrying out their obligations as students to achieve goals.